2021
DOI: 10.3390/ijms221810146
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Hypoxia on Osteoclast Formation and Activity: Systematic Review

Abstract: Hypoxia is evident in several bone diseases which are characterized by excessive bone resorption by osteoclasts, the bone-resorbing cells. The effects of hypoxia on osteoclast formation and activities are widely studied but remain inconclusive. This systematic review discusses the studies reporting the effect of hypoxia on osteoclast differentiation and activity. A literature search for relevant studies was conducted through SCOPUS and PUBMED MEDLINE search engines. The inclusion criteria were original researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…HIF proteins such as HIF-1α or HIF-2α, which are also the transcription factors that mediate hypoxia-related pathways, are often highly expressed in hypoxic circumstances. HIF-1α is constitutively hydroxylated in the presence of oxygen and is then targeted for proteasomal destruction [ 57 ]. Under hypoxic conditions, however, this does not happen, allowing HIF- 1α to stay stable in the cell and be able to dimerize with HIF- 1β before binding to the hypoxia-response element and starting the transcription of HIF target genes [ 57 ].…”
Section: Osteometabolism: Metabolic Requirements Of Bone Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…HIF proteins such as HIF-1α or HIF-2α, which are also the transcription factors that mediate hypoxia-related pathways, are often highly expressed in hypoxic circumstances. HIF-1α is constitutively hydroxylated in the presence of oxygen and is then targeted for proteasomal destruction [ 57 ]. Under hypoxic conditions, however, this does not happen, allowing HIF- 1α to stay stable in the cell and be able to dimerize with HIF- 1β before binding to the hypoxia-response element and starting the transcription of HIF target genes [ 57 ].…”
Section: Osteometabolism: Metabolic Requirements Of Bone Cellsmentioning
confidence: 99%
“…HIF-1α is constitutively hydroxylated in the presence of oxygen and is then targeted for proteasomal destruction [ 57 ]. Under hypoxic conditions, however, this does not happen, allowing HIF- 1α to stay stable in the cell and be able to dimerize with HIF- 1β before binding to the hypoxia-response element and starting the transcription of HIF target genes [ 57 ]. Studies suggest contradictory results of hypoxic conditions on osteoblastogenesis; however, the duration and concentration of hypoxic conditions need further investigation.…”
Section: Osteometabolism: Metabolic Requirements Of Bone Cellsmentioning
confidence: 99%
“…It was reported that under hypoxic conditions (e.g., 1% oxygen concentration), the proliferation and differentiation potential of osteoblasts is remarkably inhibited [ 61 , 62 ]. Furthermore, the hypoxic niche contributes significantly to the activation of osteoclasts for bone resorption [ 63 , 64 ]. Therefore, further investigations of the synergistic effects of oxygen and Sr 2+ released by the developed scaffold system are warranted in terms of promoting osteoblast proliferation/differentiation and suppressing osteoclast formation to further highlight the potential benefits of SrO 2 + MnO 2 @PLGA/gelatin.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we focus on the changes in mitochondrial bioenergetic parameters, glycolysis efficiency, and profile of substrates fueling mitochondrial respiration during PE-induced osteoclast differentiation, and how these could be affected by TRF treatment. From our published systematic review [ 53 ]—even though a majority of the literature has reported an increase in osteoclastogenesis following hypoxia—some studies have indicated otherwise. This may suggest that both aerobic and anaerobic respiration are important during osteoclastogenesis; hence, both OXPHOS and glycolysis, as well as the oxidation of metabolic substrates, should be examined in osteoclasts.…”
Section: Introductionmentioning
confidence: 99%